Breeding annual grain legumes for sustainable agriculture: New methods to approach complex traits and target new cultivar ideotypes - Duc, G.; Agrama, H.; Bao, S.; Berger, J.; Bourion, V.; Ron, A.M. de; Gowda, C.L.L.; Mikic, A.; Millot, D.; Singh, K.B.; Tullu, A.; Vandenberg, A.; et al. (Informa UK Limited, 2015)
Although yield and total biomass produced by annual legumes remain major objectives for breeders, other issues such as environment-friendly, resource use efficiency including symbiotic performance, resilient production in the context of climate change, adaptation to sustainable cropping systems (reducing leaching, greenhouse gas emissions and pesticide residues), adaptation to diverse uses (seeds for feed, food, non-food, forage or green manure) and finally new ecological services such as pollinator protection, imply the need for definition of new ideotypes and development of innovative genotypes to enhance their commercialization. Taken as a whole, this means more complex and integrated objectives for breeders. Several illustrations will be given of breeding such complex traits for different annual legume species. Genetic diversity for root development and for the ability to establish efficient symbioses with rhizobia and mycorrhiza can contribute to better resource management (N, P, water). Shoot architectures and phenologies can contribute to yield and biotic constraint protection (parasitic weeds, diseases or insects) reducing pesticide use. Variable maturity periods and tolerance to biotic and abiotic stresses are key features for the introduction of annual legumes to low input cropping systems and for enlarging cultivated area. Adaptation to intercropping requires adapted genotypes. Improved health and nutritional value for humans are key objectives for developing new markets. Modifying product composition often requires the development of specific cultivars and sometimes the need to break negative genetic correlations with yield. A holistic approach in legume breeding is important for defining objectives with farmers, processors and consumers. The cultivar structures are likely to be more complex, combining genotypes, plant species and associated symbionts. New tools to build and evaluate them are important if legumes are to deliver their exciting potential in terms of agricultural productivity and sustainability as well as for feed and food.